1994
DOI: 10.1300/j083v21n01_08
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Abuse and Medication Misuse in Older Adults As Estimated by Service Providers

Abstract: Staff providing services to older adults in Florida andNorth Carolina were asked to estimate the prevalence of alcohol abuse and medication misuse among their clients. Although there, were high prevalence rates in both states, Florida estimates were greater, especially by staff offering on-site rather than in-home services. Estimates of direct ,care and administrative staff did not differ. Few staff received in-service training on substance abuse issues, despite ranking the topics of "medication misuse" and "c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Earlier studies found much higher rates of alcohol use disorders in hospital and psychiatric in-patients compared with communitydwelling prevalence rates (Schonfeld, et al, 1993;Goldstein, et al, 1996). Earlier studies found much higher rates of alcohol use disorders in hospital and psychiatric in-patients compared with communitydwelling prevalence rates (Schonfeld, et al, 1993;Goldstein, et al, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Earlier studies found much higher rates of alcohol use disorders in hospital and psychiatric in-patients compared with communitydwelling prevalence rates (Schonfeld, et al, 1993;Goldstein, et al, 1996). Earlier studies found much higher rates of alcohol use disorders in hospital and psychiatric in-patients compared with communitydwelling prevalence rates (Schonfeld, et al, 1993;Goldstein, et al, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…Although substance abuse represents a major public health problem and presents increased risks to older adults, to date little attention has focused on older adults with substance abuse problems or on the potential efficacy of interventions to address the needs of this population (Atkinson, 1990;Schonfeld, Rohrer, Zima, & Spiegel, 1993). As the population continues to age, social work practitioners and researchers will increasingly confront the needs of older adults with substance abuse disorders.…”
mentioning
confidence: 99%
“…There were two venues for service: either in-home care was provided, or the client was seen at an agency. Less than 2% of the admissions to alcohol treatment programs are seniors, even though estimates of alcohol abuse in this age group range from 2% to 15% or more (Schonfeld et al, 1993). The results of this study provided estimates for alcohol abuse that ranged from 1% (North Carolina, in-home) to 26% (Florida, agency), and estimates for medication abuse from 18% (North Carolina, agency) to 41% (Florida, agency).…”
Section: B) Patternsmentioning
confidence: 80%
“…® be unable to read the instructions on the bottle; and ® not get the prescription refilled either because they cannot afford it or because they do not think they need it as they feel fine (Ruben, 1992). Schonfeld, Rohrer, Zima and Spiegel (1993) initiated a study of substance use problems in seniors because of concerns that they are a hidden population. The researchers interviewed service providers in Florida and North Carolina and asked them to estimate the percentage of their clients that they felt had alcohol or medication problems.…”
Section: B) Patternsmentioning
confidence: 99%